Entropy formation in second grade nanofluid flow across a curved surface with the impact of activation energy and chemical reaction - Ikram Ullah; Asif Ullah Hayat; Mohammad Mahtab Alam; Marouan Kouki; Hamda Khan; Hijaz Ahmad (Case Studies in Thermal Engineering)
The heat and mass transfer through the second-grade nanofluid across a curved surface is investigated in the present article with the consequences of chemical reaction, activation energy and Ohmic heating. The Buongiorno model is employed to simulate the thermophoretic and Brownian diffusions effect. The flow phenomena for second-grade fluid (SGF) have been modelled in the form of system of partial differential equations (PDEs) which are converted into a system of ordinary differential equations (ODEs) by substituting the similarity variables. The model equations are converted into a system of ODEs by inserting a suitable variable. The set of dimensionless equations along with boundary conditions are evaluated computationally through the numerical differential equation solver (ND Solve) technique. The entropy optimization, energy curve, Nusselt number, mass transfer, Sherwood number, velocity and skin friction are computed and examined versus distinct physical parameters. The finding reveals that the concentration and velocity profile exhibits enhancement as the curvature parameter increases, whereas an opposite trend has been found in relation to the energy outline. Furthermore, the concentration profile raises as the activation energy increased, while diminishes with the augmentation of chemical reaction.